Thermoformability characterisation of Flax reinforced polypropylene composite materials. (1st March 2020) - Dobah, Yousef; Zampetakis, Ioannis; Ward, Carwyn; Scarpa, Fabrizio
Abstract: Flax reinforced polypropylene (Flax/PP) composites are currently used as sustainable and recyclable materials in secondary load-bearing applications. This study focuses on the effects of the thermoforming parameters (temperature, dwelling time, pressure and fabricated area parameters) and moisture absorption on the mechanical and aesthetic performance of Flax/PP laminates. The manufacturing and environmental variables have been investigated following a sequential order to identify a cumulative improvement on the performance of the Flax/PP composites. Temperature and dwelling time were the parameters with greatest influence on the aesthetics and mechanical performance of the Flax/PP. The thermoforming pressure and the size of the manufacturing area were the parameters that contributed the less. Although the moisture absorption degraded the Flax/PP mechanical performance, the moisture desorption had however a negligible impact. We therefore conclude that Flax/PP thermoformed parts could be suitably produced and stored in normal room conditions.